Eksperimen Pembuatan Beliung Persegi - Akbar, Ali (Paradigma: Jurnal Kajian Budaya, 2010)
Writing a research paper does not only use three steps, such as analysis, explanation and conclusion, but it may also use analogy. It assumes two phenomena, individual or inter-related, similar. Analogizing method uses historic, ethnographic, and experimental sources. Experimental analogy, in particular, is done by duplication. For example, it is conducted by making a stone tool, which implies that there is a collective knowledge about the characteristics of the raw material and their relations to human. Despite the fact that prehistoric archeological remnants, such as the rectangular adze, were found in different areas in Indonesia, there had not been many who knew about process of making them, and the people who used them. The experimental duplication was done repetitively, gradually, and systematically. Repetition of the production of rectangular adze is made in order to be able to draw a general conclusion. The raw materials that are used are chert, metalimestone, limestone, chalcedony, jasper, and obsidian. A rectangular adze is produced after some steps are taken: firstly, preparing the raw material and the tool, secondly, shaping, and thirdly, molding.